The ‘Me-Too’ phenomenon in packaging design: a case study of Malaysian retail products / Anith Liyana Amin Nudin...[et.al] - Amin Nudin, Anith Liyana; Shamsudin, Wan Nur Khalisah; Abdul Ghafar, Izwan; Samsuri, Norsharina; Mohamed Yussof, Fatrisha (2016)
This research is conducted to identify design elements that contribute towards visual similarities in the packaging of retail products and the effects on consumer’s buying decision. A mixed method approach was employed through this study which is quantitative and qualitative methods. Visual analysis was conducted to analyze visual similarities. Three types of product packaging with six different brands has been analyzed. The survey was carried out to one hundred consumers for the data collection. From the findings, color is indicated as the main design element that contributes towards visual similarity followed by graphic layout, and main illustration or photography of the packaging design. The findings also suggest that most of the consumers agreed that there are visual similarities between the leading product and the ‘Me-Too’ packaging design. Therefore, most of the consumers will verify the brand before buying and some of them prefer to select cheaper product; which means the ‘Me-Too’ product. Finally, it can be concluded that retail products need to be distinctive and unique in order to capture consumer’s attention and this is possible by highlighting important design elements on the packaging design. Color coded products are effective in creating strong competition on the shelf and leading brands need to be advance in packaging design in ensuring their loyal consumers will not be diverting towards ‘Me-Too’ products.